Glucose-driven anisotropic heterogeneous composite hollow multi-shell material as well as preparation method and application thereof
By using glucose -driven heterosexual composite composite large -shell multi -shell materials in the drug delivery, the problem of high load and sequential delivery of macromolecular biopharmaceuticals and small molecule chemicals is solved, and the drugs are efficient and targeted. And controlled release.
Patent Information
- Application Number
- CN202411477891.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, it is difficult to achieve high load and sequential delivery of large-molecular biological drugs and small-molecular chemical drugs in drug delivery, and the drug release controllability and targeting ability are poor.
Glucose-driven anisotropic heterogeneous composite hollow multi-shell materials were used to prepare hollow multi-shell materials with anisotropic structures through selective adsorption and segmented adsorption of oily precious metal particles, combined with step-by-step calcination of O2/N2 mixed gas. Shell material. The material catalyzes reactions in glucose solutions to achieve autonomous movement and targeted release.
It achieves simultaneous high loading of macromolecule biological drugs and small molecule chemical drugs, and improves drug delivery efficiency and therapeutic effect through glucose-responsive release and targeted release.
Smart Images

Figure CN119345390A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional materials, and relates to a glucose-driven anisotropic heterogeneous composite hollow multi-shell material, a preparation method and application thereof; specifically, it relates to an application of a glucose-driven anisotropic heterogeneous composite hollow multi-shell material in the controlled release of biological drugs and molecular drugs. Background Art
[0002] Nanomaterials as carriers for drug delivery have important application prospects for the treatment of many diseases, but their weak tissue penetration ability limits the effect of drug delivery. Therefore, it is necessary to design nanocarriers with autonomous motion performance to improve the delivery efficiency of drugs at the target location and the effect of disease treatment. In recent years, artificial micro / nanomotors have attracted widespread attention from researchers. They can react physically or chemically with the surrounding environment and convert it into mechanical energy to achieve autonomous motion, thereby increasing the penetration of tissue and cell barriers, and are expected to deliver payloads such as drugs directly to diseased tissues. With the continuous deepening of research, the structure of micro / nanomotors has shown diversity, including micro / nanotubes, micro / nanowires, micro / nanorods, Janus-shaped, spiral-shaped and self-assembled polymer micro / nanomotors, etc. Among them, micro / nanomotors with anisotropy are easier to construct asymmetric fields and achieve stronger autonomous motion, showing great application potential in the fields of drug delivery, cell separation, non-invasive microsurgery, biosensing, etc.
[0003] Hollow multishell structures have the characteristics of large effective specific surface area, orderly arrangement of shells and relatively independent cavities. They are widely used in drug delivery, catalysis, photothermal water evaporation, sensors and energy storage systems. Among them, applied to drug delivery, hollow multishells can achieve efficient loading and sequential release of drugs, which is conducive to achieving sustained release of drugs and improving long-term therapeutic effects. Since the sequential template method was proposed, a variety of hollow multishell materials have been developed, and the number of shells, shell spacing, shell thickness, crystal planes, etc. can be precisely controlled. However, the current structural control is based on isotropic hollow multishell materials, and there are no examples of research on anisotropic hollow multishell materials.
[0004] A review published in Nat. Rev. Chem (Nat. Rev. Chem. 2020, 4, 159-168.) provides an outlook on smart and dynamic HoMS, and believes that constructing anisotropic HoMS can adjust the direction of material transfer (including reactants and products), construct an uneven material concentration field around the material, and generate asymmetric forces, thereby improving autonomous movement capabilities and realizing self-driven movement and directional movement; at the same time, while ensuring a high load, it improves its ability to achieve targeted drug transport and responsive release. Summary of the invention
[0005] In view of the above shortcomings, the present invention provides a preparation method and application of anisotropic heterogeneous composite hollow multi-shell material driven by glucose, wherein the noble metal nanoparticles are fixed inside the solid precursor by selective adsorption of oily noble metal particles; by segmented adsorption, one or more metal ions are distributed in a concentration gradient on the anisotropic template, and the O2 content is further controlled for step-by-step calcination, so that different metal oxides or metal oxides and carbon layers are solidified into shells step by step, thereby obtaining anisotropic heterogeneous composite hollow multi-shell material loaded with noble metals. The hollow multi-shell can catalyze the decomposition of glucose to produce an asymmetric concentration distribution, realize directional movement and chemotaxis, and improve the glucose-responsive release and targeted release of drugs.
[0006] On the one hand, the present invention aims at the problem of low loading amount and release order when the macromolecular biological drug bevacizumab (BVZ) and the small molecule chemical drug doxorubicin hydrochloride (DOX) are co-loaded, and an anisotropic heterogeneous composite hollow multi-shell structure is constructed. The heterogeneous composite components of the hollow multi-shell structure are conducive to forming different interaction forces with chemical drugs, such as hydrogen bonds and van der Waals forces, and realize high loading of small-sized chemical drugs through shells and holes. At the same time, the anisotropic channels generated by its anisotropic structure provide space for the entry of large-sized biological drugs, realizing high loading and sequential delivery of biological drugs and chemical drugs. The preferentially released bevacizumab can inhibit tumor angiogenesis, promote vascular normalization, block glucose supply, facilitate the subsequent release of doxorubicin hydrochloride to play a role, and induce cell apoptosis. And compared with spherical Isotropic structure, the anisotropic channel can limit the rapid release of biological drugs, increase its sustained release time, and realize the three-stage release of biological drugs: sudden release, sustained release, and gradual equilibrium. On the other hand, in order to address the problems of poor controllability and poor targeting of drug release, a glucose-driven anisotropic heterogeneous composite hollow multi-shell structure was constructed. The hollow multi-shell structure can undergo catalytic reactions in glucose solutions, and its anisotropic structure can induce asymmetric distribution of catalytic products, construct an asymmetric field, and realize autonomous movement. By changing the concentration of glucose in the system, the movement speed can be changed to achieve glucose-responsive release of drugs; further, when placed in a system with a glucose concentration gradient, the drug carrier can move toward high glucose concentrations to achieve chemotaxis, which can further achieve targeted release of drugs.
[0007] In order to achieve the above purpose, the present invention adopts the following technical solutions:
[0008] In a first aspect of the present invention, the present invention provides a method for preparing a glucose-driven anisotropic heterogeneous composite hollow multi-shell material, comprising the following steps:
[0009] 1) placing a carbon source aqueous solution containing a surfactant in a reaction kettle, performing a heating reaction, and obtaining an anisotropic carbon template after centrifugation, washing and drying;
[0010] 2) dispersing the anisotropic carbon template obtained in step 1) in a solution of an organic metal salt containing noble metal nanoparticles, and first adsorbing the obtained suspension in a low-temperature water bath, and then transferring it to a high-temperature heat-insulated adsorption, centrifuging, and drying to obtain a solid precursor with different hydrophilic and hydrophobic properties on the inner and outer surfaces and noble metal loaded inside;
[0011] 3) The solid precursor obtained in step 2) is placed in an O2 / N2 mixed gas for step-by-step calcination, first calcined under low temperature conditions to solidify the first metal oxide into a shell, and then calcined under high temperature conditions to solidify the second metal oxide or carbon layer into a shell, to obtain a glucose-driven anisotropic heterogeneous composite hollow multi-shell layer.
[0012] By adopting the preparation method of the present invention, using anisotropic carbon templates, through the selective loading of oily precious metal nanoparticles, segmented adsorption and step-by-step calcination in O2 / N2 mixed gas, a glucose-driven anisotropic heterogeneous composite hollow multi-shell material can be designed and prepared. The preparation method is mild, simple to operate, suitable for large-scale production, and the method has universal applicability and can be extended to the preparation of various metal oxide / carbon and metal oxide / metal oxide composite materials, and the number of shells, the loading amount of precious metals, etc. are controllable. When the prepared anisotropic hollow multi-shell material is used for drug delivery, it can achieve simultaneous high loading of macromolecular biological drug bevacizumab and small molecule chemical drug doxorubicin hydrochloride, and realize self-driven movement and chemotaxis in glucose solution, and further realize simultaneous glucose-responsive release and targeted release of chemical drugs and biological drugs.
[0013] In addition, the preparation method according to the present invention may also have the following additional technical features:
[0014] In the step 1), the shape of the anisotropic carbon template includes vase shape, bowl shape, crescent shape, badminton shape, etc.
[0015] In the step 1), the carbon source in the carbon source aqueous solution includes one or a combination of at least two of glucose, fructose, sucrose, maltose, ribose, deoxyribose and chitosan, and the concentration of the carbon source is 0.1-4M; the surfactant includes one or a combination of at least two of sodium oleate, sodium stearate, sodium laurate, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, sodium hexadecylbenzene sulfonate, polyoxyethylene dehydrated sorbitan monopalmitate, and laurel sorbitan, and the concentration of the surfactant in the precursor aqueous solution is 0.05-4mM.
[0016] In the step 2), the metal salt is one or a combination of two or more selected from ferric acetylacetonate, tannin acetylacetonate, titanium acetylacetonate, ferric acetylacetonate, zinc acetylacetonate, methyl zinc chloride, and tin acetylacetonate; the solvent of the solution is one or a combination of two or more selected from ethanol, acetone, chloroform, and toluene; the low-temperature adsorption temperature is 30-50°C, the low-temperature adsorption time is 1-8h, the high-temperature adsorption temperature is 60-100°C, and the high-temperature adsorption time is 1-12h.
[0017] In the step 2), the noble metal nanoparticles are one or a combination of at least two of gold nanoparticles, platinum nanoparticles, and palladium nanoparticles; the mass ratio of the anisotropic carbon template to the noble metal is 10:1 to 50:1; the noble metal nanoparticles are lipophilic and have a size of 2-15 nm.
[0018] In the step 3), the volume ratio of O2:N2 in the O2 / N2 mixed gas is 20:1 to 90:1; the low-temperature calcination temperature is 200-350°C, and the low-temperature insulation time is 30-120min; the high-temperature calcination temperature is 400-600°C, and the high-temperature insulation time is 30-180min.
[0019] In a second aspect, the present invention provides a glucose-driven anisotropic heterogeneous composite hollow multi-shell material obtained by the preparation method described in the first aspect, wherein the anisotropic heterogeneous composite hollow multi-shell material comprises at least one cavity and at least one shell wall, wherein different metal oxide nanoparticles or metal oxide and carbon nanoparticles are deposited on the surface of the shell wall, wherein the metal oxide comprises titanium oxide, tantalite, zinc oxide, manganese tetraoxide, iron oxide, and tin oxide, and the shape of the anisotropic heterogeneous composite hollow multi-shell material comprises a vase shape, a bowl shape, a crescent shape, or a badminton shape;
[0020] Preferably, the shell wall has 2 to 4 layers, for example, 2 layers, 3 layers or 4 layers.
[0021] Preferably, the material can catalyze glucose to react and construct an asymmetric field.
[0022] Preferably, the diffusion coefficient of the material in 50 mM glucose solution can reach 4.94 μm 2 / s, achieving autonomous movement, and its movement ability is much higher than that of the hollow ball with the same components.
[0023] Preferably, the material can continuously adjust its forward direction in a solution with a glucose concentration gradient, move toward a high glucose concentration, and achieve chemotaxis.
[0024] In a third aspect, the present invention provides a use of the glucose-driven anisotropic heterogeneous composite hollow multi-shell material as described in the first aspect in drug delivery.
[0025] According to an embodiment of the present invention, the present invention provides a glucose-driven anisotropic heterogeneous composite hollow multi-shell material, which can achieve simultaneous high loading of the biological drug bevacizumab and the chemical drug doxorubicin hydrochloride, and realize targeted delivery and responsive release of drugs through tropism and self-driven movement.
[0026] Preferably, the drug loading step is as follows: placing the glucose-driven anisotropic heterogeneous composite hollow multi-shell material in a mixed solution of doxorubicin hydrochloride and bevacizumab for vacuum loading, the drug concentration is 1-5 mg / mL, the vacuum conditions are a vacuum degree of -1--30 bar, the loading temperature is room temperature, the loading time is 10h-24h, and after centrifugation, washing with water to remove the unloaded drug to obtain a drug-loaded hollow multi-shell material.
[0027] Preferably, the drug release step is as follows: placing the drug-loaded hollow multi-shell material in a phosphate buffer solution (PBS) (pH=6.5) containing different glucose concentrations, centrifuging to obtain 200 μL of supernatant at specific intervals, and adding 200 μL of fresh solution, determining the drug concentration in the supernatant by UV-visible absorption spectroscopy, and calculating the drug release amount.
[0028] Preferably, the material can only release 24% doxorubicin and 43% bevacizumab in PBS solution within 48 hours, while when the glucose concentration in the PBS solution is increased to 4.5 mM, the release rates of doxorubicin and bevacizumab are increased to 39% and 53%, respectively.
[0029] Compared with the prior art, the advantages of the present invention are:
[0030] 1. The present invention adopts anisotropic carbon template, selectively loads oily noble metal nanoparticles, enhances adsorption in sections and calcines in O2 / N2 mixed gas step by step to prepare glucose-driven anisotropic heterogeneous composite hollow multi-shell materials. The heterogeneous composite components of the hollow multi-shell structure are conducive to forming different interaction forces with the chemical drug doxorubicin hydrochloride, such as hydrogen bonds and van der Waals forces, and realize high loading of small-sized chemical drugs through shells and holes. At the same time, its asymmetric cavity provides space for the entry of large-sized biological drugs, which is conducive to achieving high loading of biological drugs and chemical drugs.
[0031] 2. The glucose-driven anisotropic heterogeneous composite hollow multi-shell material prepared by the present invention has different hydrophilic and hydrophobic properties on its surface, which realizes the selective loading of precious metals inside, which is conducive to the efficient glucose oxidation reaction. The anisotropic structure can realize the uneven distribution of chemical substances in the catalytic process, construct an asymmetric field, and realize the self-driven movement of the material. The diffusion coefficient can reach 4.94μm in 50mM glucose solution. 2 / s, and its movement ability is much higher than that of hollow spheres with the same components. In addition, when placed in a system with a glucose concentration gradient, the multi-shell material can sense the location of glucose and move toward high glucose to achieve chemotaxis.
[0032] 3. The glucose-driven anisotropic heterogeneous composite hollow multi-shell material prepared by the present invention has a multi-level shell that gives a higher chemical and biological drug loading capacity. When applied to drug delivery, its anisotropic pores are conducive to limiting the rapid release of the macromolecular biological drug bevacizumab, improving its sustained release time, and realizing the three-stage release of biological drugs, namely, sudden release, sustained release, and gradual balance while realizing the three-stage release of chemical drugs. By regulating the glucose concentration, the autonomous movement ability can be regulated to achieve glucose-responsive drug release. The material can only release 24% doxorubicin and 43% bevacizumab in PBS solution within 48 hours, while when placed in a PBS solution containing 4.5mM glucose concentration, the release rates of doxorubicin and bevacizumab are increased to 39% and 53%, respectively. In addition, the autonomous movement of the above-mentioned multi-shell structure can improve the permeability to tissues and improve the therapeutic effect of drugs. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a transmission electron microscope image of the glucose-driven vase-shaped anisotropic double-shell TiO2 / C prepared in Example 1.
[0034] Figure 2 This is the XRD pattern of the glucose-driven vase-shaped anisotropic double-shell TiO2 / C prepared in Example 1.
[0035] Figure 3 This is a transmission electron microscope image of the bowl-shaped anisotropic double-shell ZnO / Mn3O4 composite material prepared in Example 2.
[0036] Figure 4 This is the XRD pattern of the bowl-shaped anisotropic double-shell ZnO / Mn3O4 composite material prepared in Example 2.
[0037] Figure 5 This is a transmission electron microscope image of the glucose-driven badminton-shaped anisotropic double-shell Ta2O5 / C composite material prepared in Example 3.
[0038] Figure 6 Transmission electron microscope image of anisotropic double-shell Ta2O5 / C composite material prepared by one-time adsorption and calcination.
[0039] Figure 7 The motion trajectory of the glucose-driven crescent-shaped anisotropic double-shell Fe2O3 / ZnO composite material prepared in Example 4 in 50 mM glucose and the motion trajectory of the glucose-driven isotropic double-shell Fe2O3 / ZnO hollow sphere were used as comparisons.
[0040] Figure 8 This is the chemotactic movement trajectory of the glucose-driven crescent-shaped anisotropic double-shell Fe2O3 / ZnO composite material prepared in Example 4 towards glucose.
[0041] Fig. 9 The encapsulation efficiency of the glucose-driven crescent-shaped anisotropic double-shell ZnO / C composite material prepared in Example 5 for the biological drug bevacizumab and the chemical drug doxorubicin hydrochloride.
[0042] Fig.10 The glucose-driven crescent-shaped anisotropic double-shell ZnO / C composite material prepared in Example 5 realizes glucose-responsive release of the chemical drug doxorubicin hydrochloride at different glucose concentrations.
[0043] Fig.11 The glucose-driven crescent-shaped anisotropic double-shell ZnO / C composite material prepared in Example 5 realizes glucose-responsive release of the biological drug bevacizumab at different glucose concentrations.
[0044] Fig.12 The release rate of the biological drug bevacizumab from the spherical monolayer ZnO / C and crescent-shaped bilayer ZnO / C composite materials fitted by the Higuchi model in Example 5 is shown.
[0045] Fig.13 The release rates of the biological drug bevacizumab and the chemical drug doxorubicin hydrochloride from the crescent-shaped double-layer ZnO / C composite material fitted by the Higuchi model in Example 5 in 4.5 mM glucose solution. DETAILED DESCRIPTION
[0046] The present invention is further described in detail below with specific implementation modes.
[0047] Example 1
[0048] The present invention provides a method for preparing a glucose-driven anisotropic heterogeneous composite hollow multi-shell material, the method comprising:
[0049] (1) a mixed aqueous solution of 3 M ribose, 2 mM sodium oleate, and 0.125 mM polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer was hydrothermally reacted at 180° C. for 12 h, centrifuged, and dried at 60° C. for 24 h to obtain a vase-shaped anisotropic carbon template;
[0050] (2) dispersing the vase-shaped anisotropic carbon template obtained in step (1) in a 1M titanium acetylacetonate acetone solution containing gold and platinum nanoparticles, wherein the size of the gold and platinum nanoparticles is 2 nm, and the mixing mass ratio of the anisotropic carbon template to the gold and platinum nanoparticles is 10:1, first placing it in a 30° C. water bath for adsorption for 8 h, then transferring it to 90° C. for adsorption for 5 h, centrifuging it, and drying it for 24 h to obtain a solid precursor selectively loaded with gold and platinum nanoparticles;
[0051] (3) The solid precursor obtained in step (2) is placed in a tubular furnace, ventilated (the volume ratio of O2:N2 is 20:1), first heated to 200°C at 2°C / min, low-temperature calcined for 30 minutes, then heated to 400°C, high-temperature calcined for 180 minutes, and naturally cooled to obtain a vase-shaped anisotropic double-shell TiO2 / C composite material.
[0052] Transmission electron microscopy images of glucose-driven vase-shaped anisotropic double-shell TiO2 / C composites Figure 1 As shown, there is an opening and a nearly spherical bottom. Figure 2 Shown is the XRD pattern of the vase-shaped anisotropic double-shell TiO2 / C composite, corresponding to the anatase phase (JCPDS no. 21-1272).
[0053] Example 2
[0054] The present invention provides a method for preparing a glucose-driven anisotropic heterogeneous composite hollow multi-shell material, the method comprising:
[0055] (1) a mixed aqueous solution of 0.1 M glucose, 3 M deoxyribose, 0.05 mM sodium stearate, and 2.5 mM polyoxyethylene sorbitan monopalmitate was hydrothermally reacted at 180° C. for 12 h, centrifuged, and dried at 60° C. for 24 h to obtain a bowl-shaped anisotropic carbon template;
[0056] (2) dispersing the bowl-shaped anisotropic carbon template obtained in step (1) in an ethanol solution of zinc acetylacetonate and manganese acetylacetonate containing gold nanoparticles, wherein the concentration of the organic metal salt is 1 M, the size of the gold nanoparticles is 5 nm, and the mixing mass ratio of the anisotropic carbon template to the gold nanoparticles is 20:1. The mixed solution is first placed in a 40° C. water bath for adsorption for 3 h, then transferred to 60° C. for adsorption for 8 h, centrifuged, and dried for 24 h to obtain a solid precursor selectively loaded with gold nanoparticles;
[0057] (3) The solid precursor obtained in step (2) is placed in a tubular furnace, ventilated (the volume ratio of O2:N2 is 90:1), first heated to 300°C at 2°C / min, low-temperature calcined for 90 min, then heated to 500°C, high-temperature calcined for 120 min, and naturally cooled to obtain a glucose-driven bowl-shaped anisotropic double-shell ZnO / Mn3O4 composite material.
[0058] Figure 3 This is a transmission electron microscope image of the prepared bowl-shaped anisotropic double-shell ZnO / Mn3O4 composite material. Figure 4 Shown is the XRD pattern of bowl-shaped anisotropic double-shell ZnO / Mn3O4 composite material.
[0059] Example 3
[0060] The present invention provides a method for preparing a glucose-driven anisotropic heterogeneous composite hollow multi-shell material, the method comprising:
[0061] (1) a mixed aqueous solution of 0.5 M fructose, 4 M sucrose, 1.5 mM sodium laurate, and 2.5 mM sorbitan laurate was subjected to hydrothermal reaction at 180° C. for 12 h, centrifuged, and dried at 60° C. for 24 h to obtain a badminton-shaped anisotropic carbon template;
[0062] (2) dispersing the badminton-shaped anisotropic carbon template obtained in step (1) in a toluene solution containing acetylacetonate of gold and platinum nanoparticles, wherein the concentration of the organic metal salt is 1 M, the size of the gold and platinum nanoparticles is 4 nm, the mixing mass ratio of the anisotropic carbon template to the gold and platinum nanoparticles is 5:1, and the mixed solution is first placed in a 40° C. water bath for adsorption for 5 h, then transferred to 80° C. for adsorption for 12 h, centrifuged, and dried for 24 h to obtain a solid precursor selectively loaded with gold and platinum nanoparticles;
[0063] (3) The solid precursor obtained in step (2) is placed in a tubular furnace, ventilated (the volume ratio of O2:N2 is 40:1), first heated to 350°C at 2°C / min, low-temperature calcined for 30 minutes, then heated to 450°C, high-temperature calcined for 90 minutes, and naturally cooled to obtain a glucose-driven badminton-shaped anisotropic double-shell Ta2O5 / C composite material.
[0064] Figure 5 Transmission electron microscopy image of the prepared glucose-driven badminton-shaped anisotropic double-shell Ta2O5 / C composite material.
[0065] In contrast, a badminton-shaped anisotropic double-shell Ta2O5 / C composite material was prepared by the one-step adsorption and calcination:
[0066] (1) a mixed aqueous solution of 0.5 M fructose, 4 M sucrose, 1.5 mM sodium laurate, and 2.5 mM sorbitan laurate was subjected to hydrothermal reaction at 180° C. for 12 h, centrifuged, and dried at 60° C. for 24 h to obtain a badminton-shaped anisotropic carbon template;
[0067] (2) dispersing the badminton-shaped anisotropic carbon template obtained in step (1) in a mixed solution of tannin chloride, wherein the metal salt concentration is 1 M, and placing the mixed solution in a 40° C. water bath for adsorption for 20 h, centrifuging, and drying for 24 h to obtain a solid precursor;
[0068] (3) The solid precursor obtained in step (2) is placed in a tubular furnace, ventilated (the volume ratio of O2:N2 is 40:1), first heated to 450°C at 2°C / min, high-temperature calcined for 90 minutes, and naturally cooled to obtain a badminton-shaped anisotropic double-shell Ta2O5 / C composite material.
[0069] Figure 6 This is a transmission electron microscope image of anisotropic double-shell Ta2O5 / C composite material prepared by single adsorption and calcination. It can be seen from the figure that the morphology of the prepared Ta2O5 / C composite material is uneven and cannot form a multilayer structure.
[0070] Example 4
[0071] The present invention provides a method for preparing a glucose-driven anisotropic heterogeneous composite hollow multi-shell material, the method comprising:
[0072] (1) a mixed aqueous solution of 3 M glucose and 4 mM sodium hexadecylbenzene sulfonate was subjected to hydrothermal reaction at 180° C. for 12 h, centrifuged, and dried at 60° C. for 24 h to obtain a crescent-shaped anisotropic carbon template;
[0073] (2) dispersing the crescent-shaped anisotropic carbon template obtained in step (1) in a chloroform solution of ferric acetylacetonate and methyl zinc chloride containing gold and platinum nanoparticles, wherein the concentration of the organic metal salt is 1 M, the size of the gold and platinum nanoparticles is 3 nm, and the mixing mass ratio of the anisotropic carbon template to the gold and platinum nanoparticles is 30:1. The mixed solution is first placed in a 50° C. water bath for adsorption for 1 h, then transferred to 80° C. for adsorption for 5 h, centrifuged, and dried for 24 h to obtain a solid precursor selectively loaded with gold and platinum nanoparticles;
[0074] (3) The solid precursor obtained in step (2) is placed in a tubular furnace, ventilated (the volume ratio of O2:N2 is 80:1), first heated to 250°C at 2°C / min, low-temperature calcined for 120 min, then heated to 600°C, high-temperature calcined for 60 min, and naturally cooled to obtain a glucose-driven crescent-shaped anisotropic double-shell Fe2O3 / ZnO composite material.
[0075] Figure 7 The motion trajectory of the glucose-driven crescent-shaped anisotropic double-shell Fe2O3 / ZnO composite material in 50mM glucose. Compared with the hollow sphere, the anisotropic double-shell structure shows a larger motion range and stronger directionality. Figure 8 The crescent-shaped anisotropic double-shell Fe2O3 / ZnO composite material driven by glucose moves along its trajectory in the glucose concentration gradient system, constantly adjusting its direction of movement toward the high-sugar area.
[0076] Example 5
[0077] The present invention provides a method for preparing a glucose-driven anisotropic heterogeneous composite hollow multi-shell material, the method comprising:
[0078] (1) a mixed aqueous solution of 3 M ribose, 0.5 mM sodium oleate, and 2.5 M polyoxyethylene sorbitan monopalmitate was hydrothermally reacted at 180° C. for 12 h, centrifuged, and dried at 60° C. for 24 h to obtain a vase-shaped anisotropic carbon template;
[0079] (2) dispersing the vase-shaped anisotropic carbon template obtained in step (1) in a mixed solution of ethanol and toluene containing zinc acetylacetonate containing gold nanoparticles, wherein the concentration of the organic metal salt is 1 M, the size of the gold nanoparticles is 12 nm, and the mixed mass ratio of the anisotropic carbon template to the gold nanoparticles is 50:1. The mixed solution is first placed in a 40° C. water bath for adsorption for 5 h, then transferred to 100° C. for adsorption for 1 h, centrifuged, and dried for 24 h to obtain a solid precursor;
[0080] (3) The solid precursor obtained in step (2) is placed in a tubular furnace, ventilated (the volume ratio of O2:N2 is 50:1), first heated to 250°C at 2°C / min, low-temperature roasted for 60 min, then heated to 450°C, high-temperature roasted for 150 min, and naturally cooled to obtain a glucose-driven vase-shaped anisotropic double-shell ZnO / C composite material.
[0081] (4) The glucose-driven vase-shaped anisotropic double-shell ZnO / C composite material obtained in step (3) was placed in 4 mL of a mixed solution containing 2 mg / mL doxorubicin hydrochloride and 2 mg / mL bevacizumab, loaded in a vacuum of -1 bar, 25°C in the dark for 12 h, centrifuged at 9000 rpm for 5 min, and washed with water to remove the unloaded drug. The drug concentration in the supernatant before loading, after loading, and after washing was determined by UV-visible absorption spectroscopy, and the encapsulation efficiency and drug loading were calculated.
[0082] (5) The drug-loaded hollow multishell obtained in step (4) was placed in a PBS solution (pH = 6.5) with glucose concentrations of 0, 2.25, and 4.5 mM. 200 μL of supernatant was taken by centrifugation at specific intervals, and 200 μL of fresh solution was added. The drug concentration in the supernatant was determined by UV-visible absorption spectroscopy, and the drug release amount was calculated.
[0083] Fig. 9 The encapsulation efficiency of the biological drug bevacizumab (BVZ) and the chemical drug doxorubicin hydrochloride (DOX) in the glucose-driven crescent-shaped anisotropic ZnO / C composite material. As can be seen from the figure, the drug loading capacity increases with the increase in the number of shell layers. Compared with the isotropic material, the drug loading rate increases significantly. Fig.10 The release of the chemical drug doxorubicin hydrochloride from the double-shell ZnO / C composite material at different glucose concentrations. Fig.11 This is the release of the biological drug bevacizumab from the double-shell ZnO / C composite material at different glucose concentrations. From the release curve, it can be seen that the release is divided into three stages: sudden release, sustained release, and gradual equilibrium.
[0084] In comparison, glucose-driven spherical isotropic ZnO / C composites were prepared. Fig.12 To adopt the Higuchi model (Qt = K H t 1 / 2 )The release rate of the biological drug bevacizumab by the spherical monolayer ZnO / C and crescent-shaped bilayer ZnO / C composites fitted with ZnO / C can be seen. In both PBS and 4.5 mM glucose solution, the anisotropic structure effectively slowed down the burst release of the biological drug bevacizumab and increased the release amount of the drug in the sustained release and equilibrium stages. Fig.13 The release rates of bevacizumab and doxorubicin hydrochloride from crescent-shaped double-layer ZnO / C composite materials in 4.5 mM glucose solution were fitted by Higuchimodel. It can be seen that in the early stage of release, the release of bevacizumab is dominant. As the release time increases, the release rate of doxorubicin hydrochloride exceeds that of bevacizumab. This sequential release is beneficial to first improve the vascular situation in the tumor, and then increase the utilization rate of doxorubicin and improve the efficiency of cell apoptosis.
[0085] Example 6
[0086] The present invention provides a method for preparing a glucose-driven anisotropic heterogeneous composite hollow multi-shell material, the method comprising:
[0087] (1) a mixed aqueous solution of 2 M deoxyribose, 0.1 mM sodium stearate, and 3 M polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer was subjected to hydrothermal reaction at 180° C. for 12 h, centrifuged, and dried at 60° C. for 24 h to obtain a vase-shaped anisotropic carbon template;
[0088] (2) dispersing the vase-shaped anisotropic carbon template obtained in step (1) in a toluene solution of tin acetylacetonate containing gold and platinum nanoparticles, wherein the concentration of the organic metal salt is 1 M, the size of the gold and platinum nanoparticles is 7 nm, and the mixing mass ratio of the anisotropic carbon template to the gold nanoparticles is 40:1. The mixed solution is first placed in a 30° C. water bath for adsorption for 2 h, then transferred to 90° C. for adsorption for 6 h, centrifuged, and dried for 24 h to obtain a solid precursor;
[0089] (3) The solid precursor obtained in step (2) is placed in a tubular furnace, ventilated (the volume ratio of O2:N2 is 30:1), first heated to 350°C at 2°C / min, low-temperature calcined for 60 min, then heated to 450°C, high-temperature calcined for 90 min, and naturally cooled to obtain a glucose-driven vase-shaped anisotropic double-shell SnO2 / C composite material.
[0090] Any contents not described in detail in the present invention can be based on the conventional technical knowledge in the art.
[0091] The applicant declares that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention, which does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a glucose-driven anisotropic heterogeneous composite hollow multi-shell material, comprising the following steps: 1) placing a carbon source aqueous solution containing a surfactant in a reaction kettle, performing a heating reaction, and obtaining an anisotropic carbon template after centrifugation, washing and drying; 2) dispersing the anisotropic carbon template obtained in step 1) in a solution of an organic metal salt containing oily noble metal nanoparticles, and first adsorbing the obtained suspension in a low-temperature water bath, and then transferring it to a high-temperature heat-insulated adsorption, centrifuging, and drying to obtain a solid precursor with different hydrophilic and hydrophobic properties on the inner and outer surfaces and noble metal loaded inside; 3) The solid precursor obtained in step 2) is placed in an O2 / N2 mixed gas for step-by-step calcination, first calcined under low temperature conditions to solidify the first metal oxide into a shell, and then calcined under high temperature conditions to solidify the second metal oxide or carbon layer into a shell, to obtain a glucose-driven anisotropic heterogeneous composite hollow multi-shell layer.
2. The preparation method according to claim 1, characterized in that: In the step 1), the shape of the obtained anisotropic carbon template includes vase shape, bowl shape, crescent shape or badminton shape.
3. The preparation method according to claim 1, characterized in that: In the step 1), the carbon source comprises one or a combination of at least two of glucose, fructose, sucrose, maltose, ribose, deoxyribose and chitosan, and the concentration of the carbon source aqueous solution is 0.1-4M; The surfactant includes one or a combination of at least two of sodium oleate, sodium stearate, sodium laurate, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, sodium hexadecylbenzene sulfonate, polyoxyethylene sorbitan monopalmitate, and sorbitan laurate, and the concentration of the surfactant in the precursor aqueous solution is 0.05-4mM.
4. The preparation method according to claim 1, characterized in that: In the step 2), the metal salt is one or a combination of two or more selected from ferric acetylacetonate, tannin acetylacetonate, titanium acetylacetonate, manganese acetylacetonate, zinc acetylacetonate, methyl zinc chloride, and tin acetylacetonate; the solvent of the solution is one or a combination of two or more selected from ethanol, acetone, chloroform, and toluene; the low-temperature adsorption temperature is 30-50°C, the low-temperature adsorption time is 1-8h, the high-temperature adsorption temperature is 60-100°C, and the high-temperature adsorption time is 1-12h.
5. The preparation method according to claim 1, characterized in that: In the step 3), the volume ratio of O2:N2 in the O2 / N2 mixed gas is 20:1 to 90:1; the low-temperature calcination temperature is 200-350°C, and the low-temperature insulation time is 30-120min; the high-temperature calcination temperature is 400-600°C, and the high-temperature insulation time is 30-180min.
6. The preparation method according to claim 1, characterized in that: In the step 2), the precious metal nanoparticles used are one or a combination of at least two of gold nanoparticles, platinum nanoparticles, and palladium nanoparticles; the mass ratio of the anisotropic carbon template to the precious metal is 10:1 to 50:1; the precious metal nanoparticles are lipophilic and have a size of 2-15 nm.
7. A glucose-driven anisotropic heterogeneous composite hollow multi-shell material, characterized in that: The glucose-driven anisotropic heterogeneous composite hollow multi-shell is prepared by the preparation method according to any one of claims 1 to 6.
8. The glucose-driven anisotropic heterogeneous composite hollow multi-shell material according to claim 7, characterized in that: The anisotropic heterogeneous composite hollow multi-shell material comprises at least one cavity and at least one shell wall, wherein different metal oxide nanoparticles or metal oxide and carbon nanoparticles are deposited on the surface of the shell wall, and the metal oxides include titanium oxide, tantalite, zinc oxide, manganese tetraoxide, iron oxide, and tin oxide; The shape of the anisotropic heterogeneous composite hollow multi-shell material includes vase shape, bowl shape, crescent shape or badminton shape; Preferably, the shell wall has 2 to 4 layers, for example, 2 layers, 3 layers or 4 layers.
9. Use of the glucose-driven anisotropic heterogeneous composite hollow multi-shell material according to claim 7 or 8 in controllable drug delivery, characterized in that: The anisotropic hollow multi-shell layer can realize self-driving in glucose solution and chemotaxis toward high sugar, and realize high loading of biological drug bevacizumab and chemical drug doxorubicin hydrochloride at the same time.